Multiplex imaging and cellular target identification of kinase inhibitors via an affinity-based proteome profiling approach - Su, Ying (2015)
MLN8237 is a highly potent and presumably selective inhibitor of Aurora kinase A (AKA) and has shown promising antitumor activities. Like other kinase inhibitors which target the ATP-binding site of kinases, MLN8237 might be expected to have potential cellular off-targets. Herein, we report the first photoaffinity-based, small molecule AKA probe capable of both live-cell imaging of AKA activities and in situ proteome profiling of potential off-targets of MLN8237 (including AKA-associating proteins). By using two mutually compatible, bioorthogonal reactions (copper-catalyzed azide-alkyne cycloaddition chemistry and TCO-tetrazine ligation), we demostrate small molecule-based multiplex bioimaging for simultaneous in situ monitoring of two important cell-cycle regulating kinases (AKA and CDK1). A broad range of proteins, as potential off-targets of MLN8237 and AKA's-interacting partners, is subsequently identified by affinity-based proteome profiling coupled with large-scale LC-MS/MS analysis. From these studies, we discover novel AKA interactions which were further validated by cell-based immunoprecipitation (IP) experiments.